Spectral parameters of electron in multi-shell open semiconductor nanotube - Makhanets, O.M.; Kuchak, А.І.; Gutsul, V.I.; Voitsekhivska, O.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The spectral parameters (resonance energies and resonance widths) of electron in multi-shell open cylindrical semiconductor nanotube are theoretically investigated within the effective mass and rectangular potentials model by using the S-matrix approach. These parameters as functions of the nanotube thickness and axial quasimomentum are analyzed for the nanostructure composed of GaAs and AlxGa₁₋xAs semiconductors